Geodiversity of amarante municipality, piauí state - Rocha, Hudson Silva; Ribeiro, Karoline Veloso; Albuquerque, Emanuel Lindemberg Silva (Geosaberes; Vol 9 No 18 (2018): May - Aug., 2018)
The Geodiversity is a thematic in growing progress. This is due to the fact that the look at the abiotic aspects of nature are increasingly sharpened, given the great environmental impacts caused by the extraction of raw materials for multiple uses. Being the geodiversity the basis for biodiversity and the most varied human activities, its use is strictly related to environmental and human health. The municipality of Amarante, in the state of Piauí, has a remarkable geological, geomorphological and pedological diversity. These aspects are directly associated to the use and occupation of the land, in which they present limitations and potentialities, which must be respected to guarantee an environmental quality in said municipality.